2021
DOI: 10.3171/2020.6.jns19287
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative MRI for newly diagnosed supratentorial glioblastoma: a multicenter-registry comparative study to conventional surgery

Abstract: OBJECTIVEIntraoperative MRI (iMRI) is used in the surgical treatment of glioblastoma, with uncertain effects on outcomes. The authors evaluated the impact of iMRI on extent of resection (EOR) and overall survival (OS) while controlling for other known and suspected predictors.METHODSA multicenter retrospective cohort of 640 adult patients with newly diagnosed supratentorial glioblastoma who underwent resection was evaluated. iMRI was performed in 332/640 cases (51.9%). Reviews of MRI features and tumor volumet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
(61 reference statements)
0
30
0
Order By: Relevance
“…The use of a robotic-assisted exoscope in combination with neuronavigation that incorporated diffusion tensor tractography (DTI) for eloquent pathway visualization, permitted for large EOR (over 78%) of contrast-enhancing tumor tissue and six-month PFS in 86% of patients [90]. These findings are comparable to recent studies on GBM surgery using other adjuncts [69,71,83]. Combined use of the exoscope and fluorescence-guided surgery is currently under active investigation.…”
Section: Exoscopementioning
confidence: 57%
See 1 more Smart Citation
“…The use of a robotic-assisted exoscope in combination with neuronavigation that incorporated diffusion tensor tractography (DTI) for eloquent pathway visualization, permitted for large EOR (over 78%) of contrast-enhancing tumor tissue and six-month PFS in 86% of patients [90]. These findings are comparable to recent studies on GBM surgery using other adjuncts [69,71,83]. Combined use of the exoscope and fluorescence-guided surgery is currently under active investigation.…”
Section: Exoscopementioning
confidence: 57%
“…iMRI was a significant predictor of GTR on multivariate analysis. However, iMRI was not an independent predictor of overall survival [83].…”
Section: Intraoperative Mrimentioning
confidence: 80%
“…45 Shah et al reported in a retrospective multicenter registry comparative study of patients with newly diagnosed glioblastoma that ioMR imaging increased the gross total resection, which in turn was associated with improved overall survival after adjustment for other prognostic factors. 228 However, ioMR imaging was not an independent predictor of overall survival in multivariate analysis. 228 Another significant aspect of the ioMR imaging procedure concerns a possible increase in surgical site infection because craniotomy patients need to be moved into unsterilized diagnostic MR scanner.…”
Section: Interstitial Chemotherapymentioning
confidence: 86%
“…228 However, ioMR imaging was not an independent predictor of overall survival in multivariate analysis. 228 Another significant aspect of the ioMR imaging procedure concerns a possible increase in surgical site infection because craniotomy patients need to be moved into unsterilized diagnostic MR scanner. We were able to identify only two reports dealing with this issue, where it was noted that the rate of surgical site infection and the frequency of new neurologic deficits after ioMR image-guided surgery were within the normal range of pediatric neuro-oncologic surgery, 229 as well as wide age ranged (1-84 years old) at the multi-theater type system.…”
Section: Interstitial Chemotherapymentioning
confidence: 86%
See 1 more Smart Citation